The Role of Parenting Styles in Treatment Stunting in Selengen Village, Kayangan District - Muhajirin, Muhammad; Hamdani, Muh; Juliani, Susan; Darawati, Diah; Aini, Hidayatul; Hendriadi, Raden; Febrian, Rifqi Aufa (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The role of parenting style plays an important role in dealing with the problem of stunting. Stunting can be influenced by low access to food and the quality of balanced nutrition which is not consumed by children regularly, and often does not have a variety. Therefore, improving diet, parenting patterns, as well as improving and accessing clean water are things that must be considered in handling stunting. Poor parenting patterns in caring for children, including feeding babies and toddlers, are also influenced by the understanding of parents, especially mothers. Therefore, there is a need for education about reproductive health and nutrition so that prospective mothers understand the importance of meeting nutritional needs during pregnancy and for the fetus, which is also important in managing stunting. The role of parents in caring for children must also be based on good and appropriate understanding so that parents know what is good or bad for their children. This research aims to describe the role of parenting styles in dealing with the problem of stunting in Selengen village, Kayangan sub-district. The research uses a qualitative approach with data collection techniques from interviews and observations. The research subjects involved Health Midwives, Nutrition Midwives, Gynecology Midwives, Posyandu cadres and children experiencing stunting in Selengen village, Kayangan sub-district. The scope of activities such as socializing the provision of additional food (PMT) and immunization.